2017
DOI: 10.1002/jor.23621
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐dependent efficacy of limb ischemic preconditioning in female rats

Abstract: ABSTRACT:Our aim was to examine the effects of ischemic preconditioning (IPC) on the local periosteal and systemic inflammatory consequences of hindlimb ischemia-reperfusion (IR) in Sprague-Dawley rats with chronic estrogen deficiency (13 weeks after ovariectomy, OVX) in the presence and absence of chronic 17beta-estradiol supplementation (E2, 20 mg kg À1 , 5 days/week for 5 weeks); sham-operated (non-OVX) animals served as controls. As assessed by intravital fluorescence microscopy, rolling and the firm adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Therefore, in this study, we tested the effect of chronic ZOL treatment in a tourniquet-induced limb ischemia model, where the role of PMN–endothelial interactions in the development of postischemic microcirculatory inflammatory reactions is well established. Here, we have shown that the reduced endogenous oestrogen levels evoked by OVX do not predispose to enhanced periosteal microcirculatory complications per se [39, 40], with the results also demonstrating that, apart from temporary exacerbation of PMN–endothelial interactions at the early stages of reperfusion, no major microcirculatory inflammatory risk could be detected after chronic ZOL treatment. Oestrogen withdrawal induces a release of TNF-alpha, which is involved in the pathomechanism of osteoporotic bone loss in women [41]; but here, we did not demonstrate between-group differences in TNF-alpha levels in the postischemic phase.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, in this study, we tested the effect of chronic ZOL treatment in a tourniquet-induced limb ischemia model, where the role of PMN–endothelial interactions in the development of postischemic microcirculatory inflammatory reactions is well established. Here, we have shown that the reduced endogenous oestrogen levels evoked by OVX do not predispose to enhanced periosteal microcirculatory complications per se [39, 40], with the results also demonstrating that, apart from temporary exacerbation of PMN–endothelial interactions at the early stages of reperfusion, no major microcirculatory inflammatory risk could be detected after chronic ZOL treatment. Oestrogen withdrawal induces a release of TNF-alpha, which is involved in the pathomechanism of osteoporotic bone loss in women [41]; but here, we did not demonstrate between-group differences in TNF-alpha levels in the postischemic phase.…”
Section: Discussionmentioning
confidence: 90%
“…The female sex steroid hormones protect against coronary heart disease as well affect the contractility and receptiveness of the uterus (194). Work has also shown that estrogen pretreatment can protect against ischemic damage and suggests it plays a part in conditioning (10,90,147). Studies on conditioning in the reproductive tract are sparse but interesting.…”
Section: The Reproductive Tractmentioning
confidence: 99%